2020
DOI: 10.5194/amt-13-5259-2020
|View full text |Cite
|
Sign up to set email alerts
|

Cloud-top pressure retrieval with DSCOVR EPIC oxygen A- and B-band observations

Abstract: Abstract. An analytic transfer inverse model for Earth Polychromatic Imaging Camera (EPIC) observations is proposed to retrieve the cloud-top pressure (CTP) with the consideration of in-cloud photon penetration. In this model, an analytic equation was developed to represent the reflection at the top of the atmosphere from above cloud, in cloud, and below cloud. The coefficients of this analytic equation can be derived from a series of EPIC simulations under different atmospheric conditions using a nonlinear re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…In addition, EPIC data have been employed to observe volcanic clouds Carn et al (2016Carn et al ( , 2018, analyze the global distribution of erythemal irradiance Herman et al (2020); Herman et al (2018a), and observe solar eclipse irradiance changes (Herman at al., 2018b). EPIC observations in the backscattering region have been used to observe and characterize the glint caused by oriented ice crystals in clouds Varnai et al (2020); , retrieve cloud properties Yang et al (2013); Yang et al (2019); Yin et al (2020), ozone Herman et al (2018a) and vegetation properties Yang et al, 2017). More EPIC-related research papers may be found here: https:// epic.gsfc.nasa.gov/science/pubs.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, EPIC data have been employed to observe volcanic clouds Carn et al (2016Carn et al ( , 2018, analyze the global distribution of erythemal irradiance Herman et al (2020); Herman et al (2018a), and observe solar eclipse irradiance changes (Herman at al., 2018b). EPIC observations in the backscattering region have been used to observe and characterize the glint caused by oriented ice crystals in clouds Varnai et al (2020); , retrieve cloud properties Yang et al (2013); Yang et al (2019); Yin et al (2020), ozone Herman et al (2018a) and vegetation properties Yang et al, 2017). More EPIC-related research papers may be found here: https:// epic.gsfc.nasa.gov/science/pubs.…”
Section: Introductionmentioning
confidence: 99%
“…Oxygen absorption has been applied to remote sensing of cloud and aerosol extensively (e.g., Fischer and Grassl, 1991;Stammes et al, 2008;Wang et al, 2008;Ferlay et al, 2010;Ding et al, 2016;Richardson et al, 2020). The EPIC's two O 2 band pairs (R 764 ∕R 780 and R 688 ∕R 680 ) are used for the retrieval of CEP (Yang et al, 2013;Davis et al, 2018a;Yang et al,2019;Yin et al, 2020) and for cloud masking over snow and ice (Zhou et al, 2020). The retrieval is based on the principle that the O 2 absorption bands are sensitive to the presence of clouds, especially high and thick clouds that reduce the absorbing air mass that light travels through while the reference channel does not.…”
Section: Introductionmentioning
confidence: 99%